Cytokines in the Genesis and Treatment of Cancer - Caligiuri, Michael A.; Lotze, Michael T. (Cancer Drug Discovery and Development, 2007)
Cytokines in the Genesis and Treatment of Cancer provides a comprehensive picture of the dual role of host responses in promoting and inhibiting tumor progression. This volume represents an important investigation into the emerging intersection of cancer biology and cancer immunology. Divided into four sections, the volume's first three parts focus on cytokines in the genesis of cancer. The final section describes the notable progress - both in animal models and humans - in demonstrating the use of cytokine or anticytokine therapies for the prevention and treatment of cancer. Cytokines in the Genesis and Treatment of Cancer brings together an impressive array of internationally distinguished investigators who are devoted to the study of cytokines and cancer. Together, they produce an insightful, comprehensive discussion of cytokines and cancer that will serve as the perfect reference for all those working in the field.